Correlates of Attitudes of Filipino Healthcare Providers’ Toward the LGBT Patients - Rubio, Rica Rose May; Echem, Rosalyn (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction. An affirming environment for LGBT patients includes the attitudes of healthcare providers (HCPs) therein to enhance the overall health and reduce disparities among the members of this population. Objective. Hence, this study aimed to determine the attitudes of the doctors and nurses toward LGBT patients in Zamboanga City, Philippines and if age, gender, religion, and marital status affect their attitudes. Method. A questionnaire was given to a sample of 396 doctors and nurses working in hospitals and health clinics who were purposely chosen to participate. Percentage distribution, weighted means, T-test, ANOVA, and Scheffé post hoc criterion for significance at p < .05 were used for data analysis. Results. The results generally showed that HCPs had positive attitudes in addressing the needs of the LGBT patients, however, 13-17% of them have preferential treatment or care for heterosexual patients which may indicate a negative attitude toward the LGBT patients. The ANOVA test and Scheffé post hoc criterion for significance revealed that age, gender, and religion contributed to the nuances in their attitudes, while marital status did not. Recommendation. The HCPs role is critical in eliminating discrimination in healthcare among the LGBT population. Hence, inclusion of LGBT health issues in medical and nursing curricula and presence of policy in health facilities for the LGBT patients are necessary to ensure gender responsive healthcare services in the Philippines Keywords: attitudes, gender, healthcare providers, LGBT health, nurses, religion